ANALISIS YURIDIS PERAN KEJAKSAAN DALAM PENUNTUTAN TERDAKWA TINDAK PIDANA KORUPSI YANG MELARIKAN DIRI KE LUAR NEGERI - Swandaru, Adief (Universitas Tadulako, 2024)
Corruption is considered an extraordinary crime, so that eradicating and handling it requires extraordinary efforts and methods. Corruption has transformed into a major crime that weakens almost all aspects of life, including health, education, the economy and law enforcement. Eradicating corruption cases consistently relies on the Law concerning the Eradication of Corruption Crimes Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. In reality, the legal process for some criminal acts of corruption seems neglected. This can be seen from the presence of defendants in criminal acts of corruption who easily leave Indonesia before the legal process is completed. The Prosecutor's Office as one of the law enforcement institutions in Indonesia is expected to be able to carry out its duties and obligations in the field of prosecution objectively, independently and free from the influence of any power in order to create clean law enforcement and for the sake of justice for the nation and state. The Prosecutor's Institute is also required to improve its performance in eradicating corruption, because so far the Prosecutor's Office has not been able to demonstrate the professionalism of its officers' performance in handling corruption cases. Based on the description above, the main problem raised in this thesis is what is the role of the prosecutor's office in prosecuting defendants of criminal acts of corruption who have fled abroad and what obstacles do prosecutors face in the process of prosecuting defendants of criminal acts of corruption who have fled abroad? overseas. The results of this research are in accordance with Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia which has been given the authority to exercise state power in the field of prosecution.